Duyarlılık analizi ile tanksavar silah sistemlerinin etkinliğinin araştırılması - Aksaç, Mustafa (My University, 2002)
In this study, it is aimed to develop a model examining the efficiency of the antitank weapons at the battalion level by means of sensitivity analysis. It is also aimed to present a new approach to how a more efficient antitank defense system can be planned at the battalion level, which consists of different types of antitank weapons. This study mainly consists of three chapters. In the first chapter, the definitions of the linear programming, formulation and solution of the linear programming model are explained. In the second chapter, the definition of sensitivity analysis, the simplicities it provided, sensitivity analysis of graphical and simplex solution are clarified. In the third chapter, a model application examining the efficiency of the antitank weapons at the battalion level by means of sensitivity analysis is presented.

Bu çalismada, Duyarlilik Analizi kullanilarak tabur seviyesinde kullanilan tanksavar silahlarinin etkinliklerini arastiran bir model gelistirilmeye çalisilmistir. Kurulacak olan model farkli özelliklere sahip olan silahlardan olusan tabur tanksavar savunmasinin rasyonel bir sekilde nasil planlanabilecegini göstermeyi amaçlamaktadir. Çalisma üç bölümde olusmaktadir. Birinci bölümde; dogrusal programlamanin tanimlari, modelin kurulmasi ve çözüm yöntemleri kisaca anlatilmistir. Ikinci bölümde; duyarlilik analizinin tanimi, sagladigi kolayliklar, grafik çözüm ve simpleks çözümün duyarlilik analizleri anlatilmistir. Üçüncü bölümde; duyarlilik analizi ile tanksavar silah sistemlerinin etkinligini arastiran örnek bir uygulama verilmistir.
Keywords: Ekonometri